2013
DOI: 10.1179/1743278213y.0000000083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of process parameters on corrosion rate of friction stir welded aluminium SiC–Gr hybrid composites

Abstract: In the present study, the influence of processing parameters of friction stir welding on the corrosion rate of the welded joints of aluminium SiC-Gr hybrid composites was investigated. The experimental results indicate that the corrosion resistance of the welded joints increases at high welding (traverse) speed and/or low values of rotational speed. These variations occur as a result of the changes in the joint microstructure, where fine grains are developed as a consequence of a relatively low heat input and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Higher the heat, faster is the cooling rate leading to dynamically recrystallized grains. This aspect results in reduction in cathodic area to anodic promoting a resistive nature against corrosion and the observation is in accordance with previous studies [40].…”
Section: Surface Morphologysupporting
confidence: 93%
“…Higher the heat, faster is the cooling rate leading to dynamically recrystallized grains. This aspect results in reduction in cathodic area to anodic promoting a resistive nature against corrosion and the observation is in accordance with previous studies [40].…”
Section: Surface Morphologysupporting
confidence: 93%
“…The effect of inert particles is to reduce the anodic area, increasing the corrosion current density due to increased graphite, zirconia, and SiC particles or lower interfacial bond strength in the composite [12]. Almomani et al [8] observed that the addition of graphite might also be a reason for the reduction in corrosion resistance at higher wt% of reinforcement because the addition of graphite increases the cathodic area, which results in an increase in anodic dissolution rate, thus increases corrosion rate, and it may also be due to the development of active micro galvanic couple between aluminum and conductive graphite particles.…”
Section: Electrochemical Behaviormentioning
confidence: 99%
“…The addition of ceramic particles may cause a localized breakdown of oxide films, which may lead to the formation of the nucleation sites to initiate the corrosion process of aluminum-based composites [7]. It has been observed from the literature that the corrosion of aluminum-based composites is significantly affected by many factors, including microstructure of the matrix material, the composition of the matrix material, reinforcement, void content, micro cracks, intermetallic brittle phase formation, residual stresses, dislocation densities at pure aluminum, bond structure between different reinforcing elements, amount of reinforcement, and also, by the method of fabrication of composites [8][9][10]. The type of dispersed phase in matrix material plays a significant role in recognizing the corrosion mechanism in a composite.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, (FSP) has been recognized as a promising technique for improvement of the microstructure, mechanical properties and corrosion resistance of cast Al-Si alloys [3,4]. A number of researchers [4][5][6][7] studied the effect of FSP on corrosion resistance and microstructure of aluminum alloys, They reported that the corrosion resistance of these alloys was improved by FSP due to significant microstructural refinement and eliminating porosity of the casting alloy.Presently, most studies have been addressed the effect of FSP/FSW parameters such as rotational speed and welding (transverse) speed on corrosion resistance of FSP and FSW zones [8][9][10][11]. Limited number of studies has been carried out on the statistical analysis of FSP/FSW parameters.…”
Section: Introductionmentioning
confidence: 99%